2021
DOI: 10.3390/ijerph18073596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Service-Learning in Project WeCan under COVID-19 in a Chinese Context

Abstract: Service-learning is a widely adopted educational pedagogy and philosophy. With the support from the Wharf (Holdings) Limited (Group), service-learning was conducted in the “Project WeCan” in Hong Kong. Prior to COVID-19, traditional service-learning was implemented with students learning in the classroom and applying their knowledge and skills to the community through providing direct face-to-face service. With the COVID-19 outbreak in the 2019–20 academic year, school lockdown measures appeared. Students had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 48 publications
4
17
0
Order By: Relevance
“…In both cases, despite the limitations of a virtual teaching, they found that, similar to traditional SL, students experienced positive growth. Similarly, Leong supported e-SL as an effective tool for working on soft skills with students, demonstrating the versatility of students to incorporate technology and to adapt to emergencies [20]. However, Winkle identified some problems from team and class discussion about the difficulties of online communication, while reflective ability and cognitive empathy scores increased during online activity [23].…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…In both cases, despite the limitations of a virtual teaching, they found that, similar to traditional SL, students experienced positive growth. Similarly, Leong supported e-SL as an effective tool for working on soft skills with students, demonstrating the versatility of students to incorporate technology and to adapt to emergencies [20]. However, Winkle identified some problems from team and class discussion about the difficulties of online communication, while reflective ability and cognitive empathy scores increased during online activity [23].…”
Section: Literature Reviewmentioning
confidence: 95%
“…Some activities such as SL have been severely affected by the pandemic and professors have been forced to rethink these activities [6,19]. Even a large number of SL programs in higher education have been cancelled or suspended, although some educational institutions have transformed the way SL was conducted [1,[20][21][22][23], for example, making transitions from traditional SL to online platforms. This is not an easy issue considering that face-to-face interaction and collaboration when performing these activities in collaboration with entities is the great value of SL.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, wellbeing measures included both psychological and subjective wellbeing. Based on previous findings suggesting beneficial impacts of SL (55,59), we hypothesized significant positive changes in students' wellbeing (Hypothesis 1) and MIL (Hypothesis 2) after their SL participation. Given the possibility that MIL and wellbeing may reinforce each other and change simultaneously, we expected reciprocal associations between MIL and wellbeing (Hypothesis 3).…”
Section: The Present Studymentioning
confidence: 99%
“…One study revealed that students taking online SL programs during the pandemic showed similar gains in leadership attributes, PYD qualities (e.g., self-identify and social competence), and life satisfaction as did those students taking traditional face-to-face SL programs pre-pandemic ( 52 ). Leung et al ( 55 ) also reported that students demonstrated significant improvements in their competence after completing an online SL program during the pandemic. In a case study on virtual SL activities during the pandemic, students expressed that they gained spiritual development such as a sense of belonging, gratitude, and love ( 53 ).…”
Section: Introductionmentioning
confidence: 98%
“…Among benefits, eSL is reported to stimulate students’ teamwork competency [ 19 ], social justice and civic attitudes [ 20 ], learning engagement, gradual increment in emotional engagement during XE-SL experiences, starting from the initial uncertainty and mixed feelings to final positive emotions [ 21 ], and life satisfaction even during challenging situations such as the COVID-19 pandemic [ 22 ]. According to the literature, eSL can facilitate the application of textbook knowledge to solve actual problems while fostering more university-to-community relationships and extending the university’s reach with the geographic dispersion of the online student populations [ 23 ].…”
Section: Introductionmentioning
confidence: 99%